Đặc điểm dịch tễ học sốt xuất huyết dengue tại Bệnh viện Trung ương Huế trong 5 năm (2009-2013) - Dung, Châu Thị Mỹ; Liên, Nguyễn Thị Nam; Hồng, Phan Nữ Diệu; Lan, Lê Thị Thanh; Hải, Trương Diên; Tina, Nguyễn Thị; Tiến, Phan Trung; Ánh, Trần Thị Thu; Khoa, Phạm Thị Minh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.